Importance of biochemistry in enzyme diagnostics and determining the properties of proteins - Рўзиева Назира Ёдгоровна (Peerian Journals Publishing, 2022)
The article provides information about the functions of biochemistry, its role in medicine, the composition and structure of proteins, their use in the laboratory
Keywords: static; specific; albumin; globulin